2007
DOI: 10.1007/s11661-007-9323-2
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion Limits of Magnesium Alloys

Abstract: Magnesium alloys are generally found to be slower to extrude than aluminum alloys; however, limited quantitative comparisons of the actual operating windows have been published. In this work, the extrusion limits are determined for a series of commercial magnesium alloys (M1, ZM21, AZ31, AZ61, and ZK60). These are compared with the limits established for aluminum alloy AA6063. The maximum extrusion speed of alloy M1 is shown to be similar to AA6063. Alloys ZM21, AZ31, ZK60, and AZ61 exhibit maximum extrusion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…As shown in Fig. 2 (c) that represents bar surfaces of AZ31 (Mg-2.7Al-0.3Zn-0.16Mn, at.%) alloy samples indirectly extruded in our laboratory at 400 C at a die-exit speed of 24 m/min and 60 m/min using an as-cast sample, the maximum extrudable speed of the as-cast AZ31 alloy sample is almost the same in the case of the direct extrusion reported by Atwell et al [2]. though the extrusion method is different.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…As shown in Fig. 2 (c) that represents bar surfaces of AZ31 (Mg-2.7Al-0.3Zn-0.16Mn, at.%) alloy samples indirectly extruded in our laboratory at 400 C at a die-exit speed of 24 m/min and 60 m/min using an as-cast sample, the maximum extrudable speed of the as-cast AZ31 alloy sample is almost the same in the case of the direct extrusion reported by Atwell et al [2]. though the extrusion method is different.…”
Section: Resultssupporting
confidence: 71%
“…2 Atwell et al [2] performed the direct extrusion into 5.4 mm round bar using commercial aluminum and magnesium alloys coated by MoS 2 based dry solid lubricant, a die with a bearing length of 1 mm, a corner radius of 0.25 mm, and a bearing angle of 0 with an extrusion ratio of 30, and reported that a commercial as-cast AZ31 alloy sample can be extruded at a die-exit speed of 20 m/min at the maximum when the extrusion is performed at 375 C, and extrusion more than 10 m/min of die-exit speed cannot be successfully employed if the extrusion is conducted at 350 C or 500 C. Although a homogenization treatment before extrusions can enhance the maximum extrusion speed of the commercial AZ31 alloy sample, low temperature extrusion at 350 C brings about high extrusion load and high temperature extrusion at 500 C easily occurs surface cracking if the extrusion speed becomes too high. For these reasons, die-exit speed over 20 m/min cannot be applied for the extrusion at 350 C and 500 C even by using the homogenized commercial AZ31 alloy sample [2]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With these alloys, extrusion is one of the most important large-scale manufacturing method. As much as a high extrusion ratio and a high extrusion speed count much in mass production, [22][23][24] the microstructure evolution and strengthening mechanism in extruded alloys have not yet been elucidated in detail. The present study attempts to clarify the influence of extrusion parameters on the microstructure evolution and mechanical properties of the LPSO phase-containing Mg 97 Zn 1 Y 2 alloys obtained at room and elevated temperatures.…”
Section: -7)mentioning
confidence: 99%
“…Several investigations studied the effects of billet temperature on the extrusion limits of magnesium and found that the limit is directly related to the magnesium-alloying components (Atwell and Barnett 2007;Davies and Barnett 2004). Furthermore, the increase in extrusion speed and load was inversely proportional to the increase in aluminum content and applied extrusion pressure and directly proportional to zinc content (Davies and Barnett 2004).…”
Section: Manufacturabilitymentioning
confidence: 99%